Clinical Outcomes After Radioiodine Therapy, According to the Method of Preparation by Recombinant TSH vs. Endogenous Hypothyroidism, in Thyroid Cancer Patients at Intermediate-High Risk of Recurrence - Higuchi, Cynara Rena Salmont; Fernanda, Paula; Jurnior, Paulo Alonso; Andrade, Fernanda Accioly; Corbo, Rossana; Vaisman, Mario; Vaisman, Fernanda; Bulzico, Daniel (Frontiers in Nuclear Medicine, 2021)
Background: To effectively treat differentiated thyroid carcinoma (DTC) with radioiodine therapy (RAI), it is necessary to raise serum thyrotropin levels, either by thyroid hormone withdrawal (THW) or by administration of recombinant human TSH (rhTSH). The use of rh-TSH is controversial in DTC patients at intermediate to high risk of recurrence. Even more controversial is the question of whether is alters progression-free survival rates and overall survival in more aggressive patients. Objective: The primary objective of this study was comparing clinical outcomes according to the method of preparation of RAI in intermediate to high DTC patients who presented progression of structural disease. Methods: This retrospective study included 81 patients with initial intermediate to high DTC and progression of structural disease at the end of follow-up. In 21 patients, all RAI treatments were done with only rhTSH stimulation. In 11, RAI treatments were done either with thyroid hormone withdrawal (THW) or rhTSH. In 49 patients, all RAI treatments were done only THW. Results: After a median follow-up time of 83 months, there were no statistical differences in the clinical outcomes (status of structural disease at the end of the follow-up, death rate, overall survival curve, and progression-free survival curve). Conclusions: Preparation for RAI therapy using either rhTSH stimulation or THW was associated with no inferiority in the clinical outcomes in progressive DTC patients at higher risk of recurrence.